Advanced therapies in Parkinson's disease: Long-term retrospective study. (August 2016) - Merola, Aristide; Espay, Alberto J.; Romagnolo, Alberto; Bernardini, Andrea; Rizzi, Laura; Rosso, Michela; Espay, Kristy J.; Zibetti, Maurizio; Lanotte, Michele; Lopiano, Leonardo
Abstract: Background: Levodopa/carbidopa intestinal gel infusion (LCIG) and subthalamic nucleus deep brain stimulation (STN-DBS) are approved therapies for advanced Parkinson's disease (PD) whose long-term comparability remains unclear. Methods: We reviewed the 5-year data on activities of daily living (ADL) and motor complications (OFF time, dyskinesia duration, and dyskinesia severity), as measured by the Unified Parkinson Disease Rating Scale (UPDRS) section-II and section-IV (items 39, 32, and 33, respectively) in 60 PD patients exposed to STN-DBS (n = 20), LCIG (n = 20), and oral medical therapy (OMT) (n = 20) at similar baseline disability and cognitive state. Results: STN-DBS and LCIG showed a similar magnitude of deterioration in ADL (+6.1 vs. +5.7 UPDRS-II; p = 0.709), but lesser than with OMT (+13.7 UPDRS-II; p = 0.005). OFF time also improved to the same extent in STN-DBS and LCIG (−62% vs. −54.5%; p = 0.830), while worsened with OMT (+78.6%; p < 0.001). STN-DBS and LCIG yielded greater improvement on dyskinesia compared to OMT (dyskinesia duration: −66.1% vs. −9.0% vs. +24.2% [ p = 0.001]; dyskinesia severity: −68.8% vs. −18.0% vs. +16.2% [ p = 0.002]), with relative superiority of STN-DBS over LCIG ( p = 0.004 for duration; p = 0.014 for severity). The annualized rate of complication was lower in STN-DBS vs. LCIG (0.13 vs. 0.68; p < 0.001) but not different between STN-DBS and OMT (0.13 vs. 0.10; p = 0.795). Conclusions: STN-DBS and LCIG showed comparable efficacy in ADL and OFF time, superior to OMT. STN-DBS yielded greater improvement in dyskinesia and lower long-term rate of complications than LCIG. Highlights: STN-DBS and LCIG were equally effective on ADL scores and OFF time. STN-DBS yielded greater improvement than LCIG on dyskinesia duration and severity. STN-DBS and Oral Treatment were associated with fewer technical and/or treatment-related complications than LCIG.